2015
DOI: 10.1007/s12687-015-0223-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the hot-spot areas for sickle cell disease using cord blood screening at a district hospital: an Indian perspective

Abstract: Abstracts Sickle cell disease (SCD), a genetic disorder often reported late, can be identified early in life, and hot-spot areas may be identified to conduct genetic epidemiology studies. This study was undertaken to estimate prevalence and to identify hot spot area for SCD in Kalahandi district, by screening cord blood of neonates delivered at the district hospital as firsthand information. Kalahandi District Hospital selected for the study is predominated by tribal population with higher prevalence of SCD as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Thirteen of the 761 newborns screened were homozygous for sickle cell disease. This study showed the feasibility of undertaking newborn screening in a district hospital which helped to identify a hot spot area for sickle cell disease in this region [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen of the 761 newborns screened were homozygous for sickle cell disease. This study showed the feasibility of undertaking newborn screening in a district hospital which helped to identify a hot spot area for sickle cell disease in this region [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, rarely, renal replacement therapy may be needed. Ahn et al 22 in a review of 22 cases, with acute intrahepatic cholestasis presenting as liver failure, showed good response in 8 of 9 patients with exchange transfusion. One patient who did not respond died after liver transplantation.…”
Section: Managementmentioning
confidence: 98%
“…20 Figure 1 summarizes district-wise distribution of the sickle cell gene among tribal populations in different states of India. The high prevalence of the b s allele frequency within scheduled groups is probably due to a combination of three factors: (i) a potentially greater selection pressure on these groups from malaria; 21 (ii) the high rate of endogamy is observed in the scheduled group; 22 (iii) a competitive evolutionary exclusion of b s occurs in certain nonscheduled groups. 23,24 The sickle cell carrier frequency in the scheduled population ranges from 1 to 40%, whereas that in the nonscheduled population is usually <5%.…”
Section: Epidemiology Of Scd In Indiamentioning
confidence: 99%
“…Religious restrictions compounded by the geographical isolation of some Indian habitats due to the country's diverse topography have contributed significantly to a relatively higher rate of inbreeding (population-inbreeding coefficient of India = 0.00-0.20) and, thus, served as barriers to random mating and free gene flow leading to the distinct gene pool of the Indian sub-populations (Bittles et al, 2002). In parallel, there is also a relatively higher burden of specific diseases (Bittles, 2002a;Mcelreavey et al, 2005;Pradhan et al, 2011;Dixit et al, 2015). A list of some of the disease-associated founder variations determined from the Indian population has been indicated in Table 2 Table 3).…”
Section: India As a Trove Of Genetic Disordersmentioning
confidence: 99%